Comparison of Generic‐to‐Brand Switchback Rates Between Generic and Authorized Generic Drugs. Issue 4 (20th March 2017) - Hansen, Richard A.; Qian, Jingjing; Berg, Richard; Linneman, James; Seoane‐Vazquez, Enrique; Dutcher, Sarah K.; Raofi, Saeid; Page, C. David; Peissig, Peggy
Abstract : Study Objective: Generic drugs contain identical active ingredients as their corresponding brand drugs and are pharmaceutically equivalent and bioequivalent, whereas authorized generic drugs (AGs) contain both identical active and inactive ingredients as their corresponding brand drugs but are marketed as generics. This study compares generic‐to‐brand switchback rates between generic and AGs. Design: Retrospective cohort study. Data Source: Claims and electronic health record data from a regional U.S. health care system. Patients: The full cohort consisted of 5542 unique patients who received select branded drugs during the 6 months prior to their generic drug market availability (between 1999 and 2014) and then were switched to an AG or generic drug within 30 months of generic drug entry. For these patients, 5929 unique patient‐drug combinations (867 with AGs and 5062 with generic drugs) were evaluated. Measurements and Main Results: Ten drugs with AGs and generics marketed between 1999 and 2014 were evaluated. The date of the first generic prescription was considered the index date for each drug, and it marked the beginning of follow‐up to evaluate the occurrence of generic‐to‐brand switchback patterns over the subsequent 30 months. Switchback rates were compared between patients receiving AGs versus those receiving generics using multivariable Cox proportional hazards models, controlling for individual drug effects, age, sex, Charlson Comorbidity Score, pre‐index drug use characteristics, and pre‐index health care utilization. Among the 5542 unique patients who switched from brand to generic or brand to AG, 264 (4.8%) switched back to the brand drug. Overall switchback rates were similar for AGs compared with generics (hazard ratio [HR] 0.86, 95% confidence interval [CI] 0.65–1.15). The likelihood of switchback was higher for alendronate (HR 1.64, 95% CI 1.20–2.23) and simvastatin (HR 1.81, 95% CI 1.30–2.54) and lower for amlodipine (HR 0.27, 95% CI 0.17–0.42) compared with the other drugs evaluated. Conclusion: Overall switchback rates were similar between AG and generic drug users, indirectly supporting similar efficacy and tolerability profiles for brand and generic drugs. Reasons for differences in switchback rates among specific products need to be explored further.